2016
DOI: 10.5812/jjnpp.32422
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Sea Cucumber (Stichopus variegatus) Body Wall Extract in Chabahar Bay, Oman Sea

Abstract: Background: Seas and oceans have been recognized as a rich source of metabolites and bioactive compounds with biodiversity and drug activity. These compounds have accumulated in various organisms. Bioactive compounds can be extracted from various animal groups, such as coral, crabs, moss animals, Echinodermata, case-bearers, fishes, and sponges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…On the other hand, there is an essential and continuous demand to extract new secondary metabolites with a variety of chemical structures of sea cucumbers with potential antibacterial activities (Hamayeli et al 2019). Also, it seems that sea cucumber species, extract types, as well as bacterial strains are effective in forming the growth inhibition zone (Shakouri et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, there is an essential and continuous demand to extract new secondary metabolites with a variety of chemical structures of sea cucumbers with potential antibacterial activities (Hamayeli et al 2019). Also, it seems that sea cucumber species, extract types, as well as bacterial strains are effective in forming the growth inhibition zone (Shakouri et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, it seems that species of sea cucumbers, extract types, and different extract concentrations can be effective in antibacterial properties. The discrepancy in the effect of sea cucumbers on different bacterial strains is associated with different amino acid sequences extracted from them (Shakouri et al 2017). These results are in agreement with earlier reports proved that different concentrations of extracts from sea cucumber species have been effective in antimicrobial properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past few years, numerous investigations on the antibacterial properties of various sea species have been conducted in many different nations (Shakouri et al 2017). The search and discovery of natural antibacterial compounds have been increasingly reported worldwide.…”
Section: Antibacterial Activities Of Dolabella Auricularia Egg String...mentioning
confidence: 99%
“…The antifungal activity of Holothuria polii was investigated and results showed that the ethanol extract of the body wall of the mentioned sea cucumber species has a potent antifungal activity on A. flavus, A. niger, and C. albicans in a concentration of 2.5mg/mL (Omran and Allam 2013). On the other hand, the methanol and aqueous methanol extract of S. variegatus has an inhibitory effect against A. niger in the concentration of 1-8mg/mL (Shakouri et al 2017). Adibpour et al (2014) examined the antifungal activity of Holothuria leucospilota.…”
mentioning
confidence: 99%